Sustainable Wellness Tourism in Indonesia (Case Study on Health Tourism Development at Hanara Wellbeing Center Bandung) - Albasrie, Astri Dwi Andriani; Himawan, Irfan Sophan; Sharipudin, Mohamad Noor Salehhuddin Bin (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Wellness tourism is currently developing and starting to be recognized as an important aspect of tourism. Not only in Bali, Bandung is developing itself into a destination for foreign tourists for wellness tourism. Wellness tourism, which focuses on activities and experiences aimed at enhancing one's health and well-being, is intricately linked with sustainable tourism principles. This phenomenon is then studied using constructivist paradigms, qualitative methods, case study approaches, and social construction theory. Data collection techniques were participant observation for a year, interviews with 6 key informants and triangulation of 19 sources, literature study, and document study. The purpose of this study is to determine the development of wellness tourism in Bandung, Indonesia. The results showed that Bandung is an alternative to wellness tourism, because it was visited by patients from Malaysia, Canada, Singapore, Switzerland, the Philippines, Pakistan, Timor Leste and Australia. The uniqueness is: 1) Offering holistic health care; 2) Organizing complementary and alternative medicine under the supervision of doctors; 3) Spiritual healing-based care; 4) Teaching patients self-healing methods; 5) Not using chemical drugs; 6) Leaving the paternalistic model ;7) loyal patients are fostered in a community; and 8) using celebrities in promotions.